Constructive Empathizing – Educational Competence in the Light of Child’s Play - Kaczmarczyk, Lech (ETHICS IN PROGRESS, 2013)
Pre-school play is an important moment in a child’s development. Caretakers play an important role during play. This article presents a structure of educational competence called “constructive empathizing” or “invitingaccompanying competence”. A caretaker’s special task during child’s play is conversion between the third-person knowledge and a subjective, autotelic interaction. The caretaker’s constructive empathizing during a child’s play determines the child’s social and moral development, it helps the child to turn play into work, as a sign of higher spontaneous understanding of cultural norms standing behind cultural correctness actions. Finally, it is evidence of dynamic interaction between abstract-concrete thinking, with the child learning from the caretaker.